2021
DOI: 10.1021/acs.jpcb.1c08844
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Ultrafast Access to a Solvent-Independent Singlet–Triplet Equilibrium State in Acridone Solutions

Abstract: Acridone and its derivatives have potential application as emitters for highly efficient blue organic light-emitting diodes (OLEDs). In this paper, we demonstrated ultrafast access of a solvent-independent singlet−triplet equilibrium state in acridone solutions by using femtosecond time-resolved spectroscopy. Our spectral data show that due to highly effective forward and reverse intersystem crossing (both k ISC and k rISC over 10 10 s −1 ), a singlet−triplet equilibrium state is always populated in acridone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Their electron configuration was carefully examined and revealed with nπ* and ππ*character, respectively. These results indicate that the intersystem crossing can proceed efficiently via the pathway of S 2 → S 1 → T 1 (ππ*), which is consistent with the results from QM/MM molecular dynamics simulations and high-level ab initio calculations, and ultrafast spectroscopic experiments for analog aromatic carbonyls. A surface-crossing point T 2 /T 1 with the energy of 77.2/77.3 kcal/mol was located, indicating that the nπ* and ππ* triplets are in equilibrium. Given that the computed energies were obtained in the gas phase and the fact that the polar solvent can stabilize the ππ* state, the nπ* triplet may have a minor population.…”
Section: Resultssupporting
confidence: 84%
“…Their electron configuration was carefully examined and revealed with nπ* and ππ*character, respectively. These results indicate that the intersystem crossing can proceed efficiently via the pathway of S 2 → S 1 → T 1 (ππ*), which is consistent with the results from QM/MM molecular dynamics simulations and high-level ab initio calculations, and ultrafast spectroscopic experiments for analog aromatic carbonyls. A surface-crossing point T 2 /T 1 with the energy of 77.2/77.3 kcal/mol was located, indicating that the nπ* and ππ* triplets are in equilibrium. Given that the computed energies were obtained in the gas phase and the fact that the polar solvent can stabilize the ππ* state, the nπ* triplet may have a minor population.…”
Section: Resultssupporting
confidence: 84%
“…17 Chen et al demonstrated ultrafast access to a singlet–triplet equilibrium state in all the acridone solutions studied, elucidating the unique photophysical behaviour of acridone. 18 Inspired by these preceding observations, we propose a photo-induced direct arylation of arenes and heteroarenes with aryl diazonium salts, triggered by the relatively inexpensive catalyst acridone.…”
Section: Introductionmentioning
confidence: 94%
“…[2][3][4] The benefits offered by acridone fluorophores are enormous: in contrast to the synthetically challenging B/N-based molecules, acridone derivatives can be readily synthesized. 5 In addition, the carbonyl group generates the n-p* transition state, [6][7][8] which provides an exciton-harvest channel that is quantum chemically allowed by the El-Sayed rule. 9 Notable successes involve quinolino[3,2,1-de]acridine-5,9dione.…”
mentioning
confidence: 99%